Enhancing career adaptability in college students: a Tai Chi-based sports intervention study - Wang, Le; Zhai, Yuanyan; Sun, Qichao (Frontiers in Psychology, 2024)
This research explores the impact of Tai Chi, a traditional Chinese martial art, on the career adaptability of college students, utilizing a quasi-experimental design. With the increasing complexities in the transition from school to work, effective interventions that address both psychological and vocational needs are essential.The study involved 70 senior college students, randomly assigned to either an intervention group that participated in an organized 8-week Tai Chi program based on positive youth development (PYD) or a control group with no intervention.Results indicated significant improvements in the intervention group in terms of both career adaptability and satisfaction of basic psychological needs, compared to the control group. Mediation analysis revealed that the increase in career adaptability induced by intervention was mediated by the satisfaction of basic psychological needs, underscoring the effectiveness of Tai Chi as a holistic intervention tool.This study contributes to the field by demonstrating that physical activity, particularly one embedded with deep cultural and philosophical significance like Tai Chi, can effectively enhance the career adaptability of college students. It advocates for the inclusion of PYD-based physical practices in developmental interventions aimed at preparing youth for the challenges of the modern workforce.